2020
DOI: 10.1037/fam0000603
|View full text |Cite
|
Sign up to set email alerts
|

War and displacement stressors and coping mechanisms of Syrian urban refugee families living in Istanbul.

Abstract: The overall purpose of this study was to achieve a contextual understanding of war and displacement stressors and coping mechanisms among urban refugee families from Syria living in Istanbul. This study was informed primarily by Walsh's family resilience framework and Weine's Family Consequences of Refugee Trauma empirical model. Qualitative family interviews were conducted with a purposive sample of 30 Syrian refugee families from the Çapa and Esenler neighborhoods of Istanbul. Data were analyzed using a grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…For children who have been exposed to conflict and displacement, the need for strong healthy, nurturing caregiver relationships may assume even greater importance [12] when other extended support systems in their lives, such as community and extended family, have been destroyed. Positive family interactions can serve as a protective factor as families face the upheaval of migration [13,14]. Studies which explored the linkages between war and parenting in ongoing humanitarian crisis highlighted the key role that parents or primary caregivers play [8].…”
Section: Introductionmentioning
confidence: 99%
“…For children who have been exposed to conflict and displacement, the need for strong healthy, nurturing caregiver relationships may assume even greater importance [12] when other extended support systems in their lives, such as community and extended family, have been destroyed. Positive family interactions can serve as a protective factor as families face the upheaval of migration [13,14]. Studies which explored the linkages between war and parenting in ongoing humanitarian crisis highlighted the key role that parents or primary caregivers play [8].…”
Section: Introductionmentioning
confidence: 99%
“…Also, according to authors (72,19] resilience was a process influenced by the good functioning of the family, the members' ability to make sense of the crisis from past and present experiences, to stay connected, to cope with the crisis, and to move forward in their lives. In other cases, therefore, family resilience was explored by particular characteristics of the family like their belief systems, organizational patterns, and communication processes [88].…”
Section: The Definition Of Resiliencementioning
confidence: 99%
“…Based on the researcher's community engagement with Syrian refugees and prior formative study of Syrian refugee families [19], the team concluded that a multiple family group approach previously used with Bosnian refugees in Chicago potentially fit well with Syrian culture. Of note, this type of family intervention is designed to include adolescents age 12 and above, with time allotted in each session for adolescents and adults to meet in separate breakout groups [33].…”
Section: Scientific Importance Of the Researchmentioning
confidence: 99%
“…Despite the family orientation of Syrian culture, there was little evidence of family interventions being developed or deployed for the refugees. The researchers initially conducted longitudinal qualitative research with 30 Syrian refugee families so as to better characterize family stressors and coping mechanisms [ 19 ]. The researchers concluded that many families may be able to benefit from a family-focused intervention.…”
Section: Introductionmentioning
confidence: 99%